2023
DOI: 10.1177/08982643231152276
|View full text |Cite
|
Sign up to set email alerts
|

Social Mediators of the Association Between Depression and Falls Among Older Adults

Abstract: Objectives To investigate the role of social factors in the association between depression and falls among older adults. Methods The sample included data from 3443 older adults from three waves of the Health and Retirement Study (2010–2014). A Lifestyle Questionnaire was used to measure social engagement, social network contact, and neighborhood social context. Mediating effects of social factors were estimated through causal mediation analysis. Results: Poorer social engagement and network contact were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The interaction between depression and falls may also be self-perpetuating. Depressive symptoms are particularly high among recurrent fallers, which may be related to the demoralizing effect of repeated falling [42]. Prospective cohort studies have reported that increased depressive symptoms were associated with increased falls [43].…”
Section: Overviewmentioning
confidence: 99%
“…The interaction between depression and falls may also be self-perpetuating. Depressive symptoms are particularly high among recurrent fallers, which may be related to the demoralizing effect of repeated falling [42]. Prospective cohort studies have reported that increased depressive symptoms were associated with increased falls [43].…”
Section: Overviewmentioning
confidence: 99%
“…Psychologically, falls among the older adult population tend to result in self-imposed limitations due to the fear of falling again [ 10 , 12 ]. These limitations lead to social isolation as individuals avoid participating in activities or even individual mobility [ 13 ]. Consequently, falls can lead to psychological conditions such as anxiety and depression [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%